2021
DOI: 10.1002/csr.2164
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay to be environmentally responsible? Investigating the effect on the weighted average cost of capital

Abstract: This research aims at investigating the effect of firms' environmental policies on the weighted average cost of capital (WACC) in order to catch capital markets' reaction towards corporate environmental commitment and effectiveness in reducing carbon emissions. We refer to the European market and analysed a sample of companies listed on the Stoxx Europe 600 Index during the timeframe 2014–2018. Our results show that capital markets have become particularly sensitive to environmental issues and therefore reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…The results in column 1 of panel A show that the coefficient of the variable carbon disclosure CD is negatively (−0.0466) and significantly related to the WACC, suggesting that firms disclosing carbon emissions have a lower cost of capital than those that do not disclose this information. Our results support the view that firms reporting their environmental responsibility are rewarded by capital providers by providing them with access to lower‐cost external finance (Lemma et al, 2019; Mariani et al, 2021). The results in column 4 of panel B show that the relationship between CD and the WACC is affected by a firm's NEF.…”
Section: Regressions Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The results in column 1 of panel A show that the coefficient of the variable carbon disclosure CD is negatively (−0.0466) and significantly related to the WACC, suggesting that firms disclosing carbon emissions have a lower cost of capital than those that do not disclose this information. Our results support the view that firms reporting their environmental responsibility are rewarded by capital providers by providing them with access to lower‐cost external finance (Lemma et al, 2019; Mariani et al, 2021). The results in column 4 of panel B show that the relationship between CD and the WACC is affected by a firm's NEF.…”
Section: Regressions Resultssupporting
confidence: 85%
“…We follow the previous literature for the selection of control variables and add those most frequently used in our equations (Bui et al, 2020;Francis & Khurana, 2005;Lemma et al, 2019;Mariani et al, 2021). We also include dividend payout (DPOUT) in the WACC Furthermore, the mean values of our proxies of the cost of capital, WACC, COE and COD, are 13%, 16.6%, and 6%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Another strand of studies finds that the implementation of environmentally virtuous practices yields more favorable access to finance (Cheng et al, 2014;Liu et al, 2021;Maaloul, 2018) and generates a lower cost of debt financing (Caragnano et al, 2020;Jung et al, 2018;Pizzutilo et al, 2020) and cost of capital (Mariani et al, 2021;Sharfman & Fernando, 2008). Albuquerque et al (2019) document a statistically and economically significant negative relationship between systematic risk and CSR quality.…”
Section: Social Responsibility and Performancementioning
confidence: 99%
“…Other studies identified positive abnormal for firms with high employee satisfaction (Becker et al, 2022; Edmans et al, 2014; Fauver et al, 2018), customer loyalty (Albuquerque et al, 2019; Luo & Bhattacharya, 2009), and social capital and trust (Fiordelisi et al, 2022; Lins et al, 2017). Another strand of studies finds that the implementation of environmentally virtuous practices yields more favorable access to finance (Cheng et al, 2014; Liu et al, 2021; Maaloul, 2018) and generates a lower cost of debt financing (Caragnano et al, 2020; Jung et al, 2018; Pizzutilo et al, 2020) and cost of capital (Mariani et al, 2021; Sharfman & Fernando, 2008). Albuquerque et al (2019) document a statistically and economically significant negative relationship between systematic risk and CSR quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We used the weighted average cost of capital (Equation ( 1)) to adjust the opportunity cost rate (i) of the project, considering the participation of third-party capital and a proxy for the systematic market risk [62].…”
Section: Opportunity Cost Ratementioning
confidence: 99%